2020
DOI: 10.1108/ijchm-04-2019-0370
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring volunteer impacts, legacy and leveraging is not “fake news”

Abstract: Purpose This study aims to explore the legacy potential of the FIFA Women’s World Cup (FWWC) 2015, for the host communities across Canada. Design/methodology/approach The mixed-methods study included a link to an online anonymous survey being sent to all volunteers at the FWWC that explored their prior volunteering experience, motivations for volunteering, perceived skill development and future volunteering intentions. Documents were reviewed, and key stakeholders were interviewed. Findings The results sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
0
7
0
1
Order By: Relevance
“…While this research demonstrates the value of the TESEF where there is a defined 'intervention' or event. Unlike physical activity interventions, MSE OCOGs have time constraints if hosts are to leverage for legacies, with OCOGs having 'sunset clauses' limiting their ability to leverage far beyond the event [24,25]. Vancouver2010 provided WAS and its stakeholders a once-in-a-life-time opportunity, with unique volunteering experiences, media exposure to raise awareness of WAS and adaptive sports, and infrastructure legacies of office space and accessible accommodation and training facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this research demonstrates the value of the TESEF where there is a defined 'intervention' or event. Unlike physical activity interventions, MSE OCOGs have time constraints if hosts are to leverage for legacies, with OCOGs having 'sunset clauses' limiting their ability to leverage far beyond the event [24,25]. Vancouver2010 provided WAS and its stakeholders a once-in-a-life-time opportunity, with unique volunteering experiences, media exposure to raise awareness of WAS and adaptive sports, and infrastructure legacies of office space and accessible accommodation and training facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Legacies are what remains after the MSE and are event-centered, while leveraging relates to the strategic planning and activities to achieve beneficial MSE outcomes [24,25]. The panoply of MSE legacies include infrastructure (stadia, roads, and transport); volunteering and sport participation growth; and enhanced destination competitiveness [7,19,26,27].…”
Section: Legacies and Leveragementioning
confidence: 99%
“…Dickson et al [45,46,76] adopted a proprietary scale based on the SEVMS [18] questionnaire. Contrary to this review, Kim [2] found that the most used instrument was the SEVMS, followed by the VMS-ISE.…”
Section: Discussionmentioning
confidence: 99%
“…A good theoretical base is essential to be able to connect the concepts that are evaluated, providing a base on which to build new knowledge and understand why different events may or may not occur [90,91]. The self-determination theory was the most used in four studies [1,12,74,89], followed by the theory of planned behavior, with three studies [46,67,70], and the theory of social exchange [66,78] and the theory of involvement of the sports fan [32,68], with two studies each. Kim and Cuskelly [79] stated the limitations of the theory of planned behavior in sports volunteering when considering a linear decisionmaking process, which does not consider changes in future intentions and behavior change over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation